Uma estratégia utilizando robótica para o ensino dos conceitos de velocidade e aceleração escalares - Costa Jr, Almir de Oliveira (2017)
This work aims at presenting the results of a research that proposed the elaboration and application of a didactic sequence using robotics as a teaching strategy in a significant learning perspective of kinematic concepts in the 1st year of Brazilian High School. Taking into account the low performance in Physics observed in Brazilian Elementary School alumni, the didactic sequence proposed in this research is an alternative capable to demonstrate and exemplify, in a contextualized way, concepts and physical phenomena intrinsic to speed and acceleration, that are usually shown only as illustrations or abstractly in traditional approaches. Usually, the presentation of these concepts in classrooms is dissociated from the students daily life and, thus, their concrete or even misunderstood interpretations are simply not taken into account. Considering this perspective, the didactic sequence was proposed as a teaching strategy based on robotics and data collection software that would allow students to observe and give a more significant meaning to their previous knowledge regarding to kinematics, such as: movement, position, shift, trajectory, speed and acceleration. The sequence was applied in the second shift of a forty four students classroom of a public technical High School in the city of Manaus. Upon the implementation of this didactic sequence, with discussions and practical experiments with robotic prototypes about concepts and physical principles regarding the phenomena under study, it was possible to verify evidences of a significant learning of concepts of speed and acceleration from the results analyzed with SOLO taxonomy and evaluation criteria from conceptual maps.